Structural Disparities in Carbon Dioxide Consumption and Trade in the World Economy - Stefan Ederer; Stefan Weingärtner (Austrian Institute of Economic Research (WIFO), 2014)
Social scientists have long argued that developed countries are more and more responsible for climate change because they externalise pollution to less developed countries. This paper offers a way to quantify climate responsibility by calculating carbon footprints and carbon balances between regions by means of an input-output analysis. We find that regions in the center of the world economy are increasingly consuming CO2 which was emitted in the periphery. Developed countries exhibit a large emission balance deficit with the less developed economies. Furthermore, we decompose carbon footprint developments between 1995 and 2007 into three effects: technical progress, shifts in the global value chain and increasing final demand. Our results show that the effect of technical progress is overcompensated by the effect of increased consumption and value chain shifts. Footprint growth in the center is strongly linked to additional pollution and technical development in the periphery. These findings challenge the prevailing view of the potential of modernisation and globalisation with regard to climate change.
Keywords: 330; Climate responsibility; carbon leakage; carbon footprint; environmental world-system theory; input-output analysis